The cytosolic tryparedoxin peroxidase from Trypanosoma cruzi induces a pro‐inflammatory Th1 immune response in a peroxidatic cysteine‐dependent manner. Issue 1 (25th January 2021) - López, Lucía; Chiribao, María Laura; Girard, Magalí C.; Gómez, Karina A.; Carasi, Paula; Fernandez, Marisa; Hernandez, Yolanda; Robello, Carlos; Freire, Teresa; Piñeyro, María Dolores
Summary: Trypanosoma cruzi cytosolic tryparedoxin peroxidase (c‐TXNPx) is a 2‐Cys peroxiredoxin (Prx) with an important role in detoxifying host cell oxidative molecules during parasite infection. c‐TXNPx is a virulence factor, as its overexpression enhances parasite infectivity and resistance to exogenous oxidation. As Prxs from other organisms possess immunomodulatory properties, we studied the effects of c‐TXNPx in the immune response and analysed whether the presence of the peroxidatic cysteine is necessary to mediate these properties. To this end, we used a recombinant c‐TXNPx and a mutant version (c‐TXNPxC52S) lacking the peroxidatic cysteine. We first analysed the oligomerization profile, oxidation state and peroxidase activity of both proteins by gel filtration, Western blot and enzymatic assay, respectively. To investigate their immunological properties, we analysed the phenotype and functional activity of macrophage and dendritic cells and the T‐cell response by flow cytometry after injection into mice. Our results show that c‐TXNPx, but not c‐TXNPxC52S, induces the recruitment of IL‐12/23p40‐producing innate antigen‐presenting cells and promotes a strong specific Th1 immune response. Finally, we studied the cellular and humoral immune response developed in the context of parasite natural infection and found that only wild‐type c‐TXNPx induces proliferation and high levels of IFN‐γ secretion in PBMC from chronic patients without demonstrable cardiac manifestations. In conclusion, we demonstrate that c‐TXNPx possesses pro‐inflammatory properties that depend on the presence of peroxidatic cysteine that is essential for peroxidase activity and quaternary structure of the protein and could contribute to rational design of immune‐based strategies against Chagas disease. Abstract : Trypanosoma cruzi cytosolic tryparedoxin peroxidase (c‐TXNPx) is a 2‐Cys peroxiredoxin (Prx) with an important role in detoxifying host cell oxidative molecules during parasite infection. We investigated their immunological properties, using a recombinant c‐TXNPx and a mutant version (c‐TXNPxC52S) lacking the peroxidatic cysteine. We demonstrate that c‐TXNPx possesses pro‐inflammatory properties that depend on the presence of peroxidatic cysteine, essential for peroxidase activity and quaternary structure of the protein, and could contribute to rational design of immune‐based strategies against Chagas disease.